PEMANFAATAN MEDIA PEMBELAJARAN AUTOGRAPH MENGGUNAKAN PENDEKATAN PROBLEM SOLVING UNTUK MENINGKATKAN KEMAMPUAN METAKOGNISI SISWA SMA - Wahyuni, Fitrah Sari (Jurnal Pengabdian Masyarakat MIPA dan Pendidikan MIPA, 2021)
Autograph Software is a special program used in learning mathematics. Autograph has the ability to make 2D and 3D graphics for material transformation, cone sections, vectors, slope, and derivatives. By using this software, users can observe how functions, graphs, equations, and calculations. Community service activities carried out at Al Fattah Private High School, especially for class XI, are expected students to understand the concept of integral applications, namely the volume of rotating objects and students' responses to mathematics learning through autograph learning media on the material of rotating objects. In this community service activity, it is hoped that class IX students can find an integral application problem solving for the volume of rotating objects. Autograph software is used to make it easier for students to understand the concept of the volume of a rotating object through two-dimensional and three-dimensional images with their metachogical abilities.